The Effectiveness of Systemic Approach in Teaching Adjectives - Wiwik Alwiah; Mansur Akil (Universitas Negeri Makassar, 2018)
This study aimed at investigating the effectiveness of the use of the systemic approach to improve students’ understanding on adjectives materials related to the use, usage, synonym, antonym, spelling, pronunciation, collocation, meaning, and order. This research employed a quasi-experimental design. The populations were the third-semester students of Muhammadiyah University of Makassar in academic year 2017/2018. The sample consisted of 40 students chosen from two classes by using purposive sampling technique then were divided into two groups, namely experimental and control group. The difference between experimental and control class was based on the teaching technique used during the treatment. While the experimental class was taught by using systemic approach, control class was taught by using the conventional method.The instruments of this research were adjective tests. The data was analyzed by using statistical analysis on SPSS for Windows 20.0 program. As per data, experimental group experienced improvement on their understanding on adjectives in terms of use, usage, meaning, spelling, pronunciation, synonym, antonym, collocation, and order indicated by the post-test mean score (77.1) which was significantly higher than that of the control class (59.7) and the gain of experimental group (31.2) which was higher than control group (17.4). Another supporting indicator is the t-test value which was higher than the t-table value (4.022 > 1.75). Furthermore, the researcher found that the element of adjective which experienced most significant increase on its mastery happened on the usage, while the lowest one was the collocation. The result of this research indicated that there was significant improvement between experimental and control class. It means that systemic approach that was applied in experimental group can improve the students’ mastery on adjectives material. Thus it was concluded that the systemic approach was effective to improve students’ on adjectives.